2017
DOI: 10.1055/s-0037-1599129
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Prediction Model for Vaginal Birth after Cesarean Delivery Reveals Unexpected Success in a Diverse American Population

Abstract: Objective To investigate the validity of a prediction model for success of vaginal birth after cesarean delivery (VBAC) in an ethnically diverse population. Methods We performed a retrospective cohort study of women admitted at a single academic institution for a trial of labor after cesarean from May 2007 to January 2015. Individual predicted success rates were calculated using the Maternal–Fetal Medicine Units Network prediction model. Participants were stratified into three probability-of-success groups: lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 14 publications
3
34
1
Order By: Relevance
“…A recent study by Maykin et al found that women with predicted success rates of <35% had actual VBAC rates that were nearly twofold higher and that obesity was not associated with increased TOLAC failures rates. 21 Similarly, our findings suggest that GWG may not have a negative impact on TOLAC success or complications as previously reported. [7][8][9] A potential explanation for our contrasting findings is the fact that previous studies used cohorts from the early 2000s.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study by Maykin et al found that women with predicted success rates of <35% had actual VBAC rates that were nearly twofold higher and that obesity was not associated with increased TOLAC failures rates. 21 Similarly, our findings suggest that GWG may not have a negative impact on TOLAC success or complications as previously reported. [7][8][9] A potential explanation for our contrasting findings is the fact that previous studies used cohorts from the early 2000s.…”
Section: Discussionsupporting
confidence: 88%
“…In a sample of 568 women undergoing TOLAC in a single academic center, actual success was compared with the SMFM prediction. No differences were found when predictions were 79% or greater, but actual success was nearly double the predicted rate at the lower estimations (29% predicted success vs 57% actual success) …”
Section: Predicting Success Versus Predicting Failurementioning
confidence: 80%
“…No differences were found when predictions were 79% or greater, but actual success was nearly double the predicted rate at the lower estimations (29% predicted success vs 57% actual success). 39…”
Section: Predicting Success Versus Predicting Failurementioning
confidence: 99%
“…They calculated predicted VBAC rates for a cohort of 568 women using the Maternal-Fetal Medicine Units Network calculator and compared those calculations with the actual VBAC rates. 20 There was no difference between the predicted and actual VBAC rate for women who were expected to have a high chance of success (79% vs 79%; P = .9989; n = 309). For women (n = 30) for whom the calculator predicted a success rate of less than 35% (mean predicted rate was 29%) the actual VBAC rate was 57% (P = .001), and for women (n = 229) who were expected to have a mean VBAC rate of 52%, the actual rate was 61% (P = .006).…”
Section: Limitations Of Vbac Success Prediction For Women With Class mentioning
confidence: 85%